Tamara M. Dijkstra, Inger N.I. Kuin, Muriel Moser and David Weidgenannt (eds) Strategies of Remembering in Greece under Rome (100 BC – 100 AD) - Karambinis, Michalis (Journal of Greek Archaeology, 2019)
This collective book is the result of a conference ‘Strategies of Remembrance in Greece under Rome,’ held at the Netherlands Institute at Athens in October 2016, and it stemmed from three research projects run in Germany and the Netherlands, in which the editors participated. It consists of 11 articles (two papers presented at the conference are not included in the volume), and geographically it is focused on the Roman province of Achaea.